No evidence for a `redshift cut-off' for the most powerful classical double radio sources - Jarvis, M; Rawlings, S; Willott, C; Blundell, K; Eales, S; Lacy, M (1999)
We use three samples (3CRR, 6CE and 6C*) to investigate the radio luminosity function (RLF) for the `most powerful' low-frequency selected radio sources. We find that the data are well fitted by a model with a constant co-moving space density at high redshift as well as by one with a declining co-moving space density above some particular redshift. This behaviour is very similar to that inferred for steep-spectrum radio quasars by Willott et al (1998) in line with the expectations of Unified Schemes. We conclude that there is as yet no evidence for a `redshift cut-off' in the co-moving space densities of powerful classical double radio sources, and rule out a cut-off at z < 2.5.